PENGARUH TEMPERATUR ANNEALING TERHADAP KEKERASAN DAN STRUKTUR MIKRO KOMPONEN THRUST WASHER DIFFERENTIAL - Anhar Wahyu; Rachmawaty Patria; Dewi Nofika Triana (ROTOR, 2018)
Annealing is a heat treatment process for the softening metallic materials, especially plain carbon steels. Based on the case study was found that thrust washer differential on the dump truck unit-machine model CWB6BLLDN2 fell up failure. Failure of the component was caused by the impact of gear differential on the differential case. The cracking of thrust washer was affected by the characteristic of materials which low resistance to impact load. Variation temperatures of annealing process are used by 825 °C, 875 °C, 925 °C, and 975 °C. Furthermore, a cooling method that been used is cooling on the furnace. Hardness test is used by Vickers hardness test with an indentation load of 200 kgf, and indentation time of 5 s. Cross section of the microstructure is examined by optical microscope. Based on the hardness test, the hardness is decreased by increasing of annealing temperature. Observation of microstructure shown changes on microstructure that been caused by increasing of annealing temperature. Keywords: Annealing, Hardness, Microstructure, Thrust washer differential